Determinación de la calidad ambiental, producto del mantenimiento de aeronaves en el hangar del Cema, para la prevención y control ambiental en el cantón Latacunga, período 2013 - Endara Cajas, José Antonio (2014)
this produce environmental impacts or problems like hydrocarbon, noise, gases and the solid and liquid waste generation, when these exceed permissible limits affect to the environmental facts of water, land, and air of the city. Through methodology, methods and techniques we can do an environmental quality determination inside to the CEMA. The first step was to do an environmental diagnostic where the field research and the observation were important in the study in order to know the daily procedures and to see the problems produced by itself….